Operation of bismuth film electrode in more acidic medium. (10th February 2015) - Dal Borgo, Sebastiano; Jovanovski, Vasko; Pihlar, Boris; Hocevar, Samo B.
Abstract: A new approach for application of bismuth film electrode (BiFE) under more acidic conditions is presented. The BiFE was prepared in-situ on a glassy carbon substrate electrode and employed for anodic stripping voltammetric measurement of Zn(II) in 0.01 mol L −1 hydrochloric acid (pH 2.0) in the presence of dissolved oxygen. The addition of potassium sodium tartrate tetrahydrate into the measurement solution resulted in significant improvement of the electroanalytical performance of BiFE via inhibition of hydrogen evolution. The BiFE revealed an excellent linear response towards Zn(II) in the examined concentration range of 10 to 100 μg L −1 with the calculated LoD of 1.3 μg L −1 associated with 300 s accumulation step and satisfactory repeatability of 4.8% (RSD). A preliminary study of simultaneous detection of selected trace metal ions, i.e. Pb(II) and Cd(II), together with Zn(II) was also carried out. Finally, the applicability of the proposed method was corroborated via measuring Zn(II) in a real tap water sample.